Komunikasi Dokter-Pasien - Alfitri, Alfitri (Mediator, 2006)
Mistakes in understanding the meaning of medical symbols result in negative impact for the patients. Futhermore, it can cause malpractice. Therefore, communication between a doctor and a patient is very essential to observe. It is because some malpractices occur due to miscommunication. Disease diagnosis through patient-doctor communication is influenced by the some understanding toward the messages. It creates an effective communication. Gap in communication between a docter and a patient can cause misunderstanding as well as misinformation for the patient on his disease. The hesitation of a doctor to inform the patient on the disease well in order to prevent emotional action of the patient and his family.